(untitled) (Global Journal of Medical Research, 2023)
Background Gynoid lipodystrophy GLD popularly known as cellulite is the result of fat deposits under the skin It is characterized by structural inflammatory and biochemical disorders of the subcutaneous tissue that cause irregular dimpling of the epidermis Among many treatments used for GLD Goldincision has proved to be effective showing more significant and satisfactory results Therefore this work aimed to describe this technique Methodology This is a multicenter observational study which analyzed the cases of 47 patients who were submitted to the Goldincision technique in 2021 using the team s protocol for assessment treatment and follow-up